2016
DOI: 10.1016/j.tra.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Operations of a shared, autonomous, electric vehicle fleet: Implications of vehicle & charging infrastructure decisions

Abstract: There are natural synergies between shared autonomous vehicle (AV) fleets and electric vehicle (EV) technology, since fleets of AVs resolve the practical limitations of today's non-autonomous EVs, including traveler range anxiety, access to charging infrastructure, and charging time management. Fleet-managed AVs relieve such concerns, managing range and charging activities based on real-time trip demand and established charging-station locations, as demonstrated in this paper. This work explores the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
231
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(239 citation statements)
references
References 9 publications
2
231
0
6
Order By: Relevance
“…They will open car travel 5 to children, elderly and the disabled [2,9,10,6]. Depending on the sce-nario, they may also trigger a substantial reduction of the total vehicle fleet [11,12,13,14,15,16,17] and substantial road capacity gains [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…They will open car travel 5 to children, elderly and the disabled [2,9,10,6]. Depending on the sce-nario, they may also trigger a substantial reduction of the total vehicle fleet [11,12,13,14,15,16,17] and substantial road capacity gains [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Chen [53] has shown that fleet-managed AVs relieve such concerns based on real-time travel demand and established charging-station locations. Their financial analysis suggests that the combined cost of charging infrastructure, vehicle capital and maintenance, electricity, insurance, and registration for a fleet of AVs ranges from $0.42 to $0.49 per occupied mile traveled.…”
Section: Av and Electric Vehiclesmentioning
confidence: 99%
“…Indeed, even nowadays is not uncommon for people to systematically opt for on-demand services in densely populated cities, when they can afford it. Because AVs fleets have no expenses with driver salaries, they can lower on-demand services prices to more affordable levels (Chen et al, 2016), making these services a natural candidate for early adoption (Wadud, 2017).…”
Section: Impacts Of Avsmentioning
confidence: 99%
“…Electric vehicles and on-demand services On-demand services are also a natural stage for the massification of electric AVs (Chen et al, 2016), as these are cheaper to operate and maintain (Egbue and Long, 2012), have zero emissions (important in an urban environment), and automatically look for a charging station when low on battery. If the aboveargued rise in vehicle-as-a-service use becomes a reality, it will have as by-product a speed up of vehicle fleet replacement, thereby facilitating the introduction of new, more fuel-efficient vehicles and technologies.…”
Section: 22mentioning
confidence: 99%